A Hubungan Indeks Massa Tubuh Dan Lengkar Lengan Atas Dengan Status Hemoglobin Pada Ibu Hamil Di Puskesmas Abadijaya Kota Depok Tahun 2024 - Liana Elfaristo; Rochmawati; Alfida Faqih; Dhea Firanti Adjie; Fairy Prudencia; Lusi Triwahyuni; Mira Fony Juliyanti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Anemia in pregnancy is commonly caused by malnutrition, leading to a decrease in hemoglobin (Hb) levels. Maternal nutritional status is a key indicator of adequate nutrient intake and plays a crucial role in preventing anemia. Poor nutritional status may impair erythropoiesis or result in dysfunctional red blood cells. Nutritional status in pregnant women can be assessed using Body Mass Index (BMI) and Mid-Upper Arm Circumference (MUAC), along with hemoglobin level measurement. This study aims to analyze the association between BMI and MUAC with hemoglobin (Hb) levels in pregnant women. A quantitative cross-sectional study desain was employed. Secondary data were obtained from hemoglobin examinations conducted in 2024. The study used total sampling technique, including101 pregnant women who underwent Hb Testting. Bivariate analysis was performed to examine the relationship between BMI, MUAC and Hb levels. The results showed no significant association between BMI and Hb levels (p=0.282), while a significant association wa found between MUAC and Hb levels (p=0.027). In conclution, BMI is not associated with Hb levels, whereas MUAC is significantly related to Hb levels in pregnant women.